Impact of fresh orange, apple, mango and papaya fruit juices on postprandial glycemia in apparently healthy young adults - Yapo Hypolithe Kouadio; Béda Frank Yapo; Jean-Brice Gbakayoro; Hadja Mawa Fatim Diabagate; Ouattara Ahmed Farman (NFS Journal)
The consumption of fruit juices remains controversial due to their potentially negative impact on postprandial glycemic response. The aim of this study was to determine the glycemic index and glycemic load of four fruit juices in apparently healthy adult subjects. This study included 16 healthy adults. Each subject consumed the reference food twice and the fruit juices once. The fruit juices studied were orange, papaya, apple, and mango, all freshly pressed with no added sugar. All juices were made from very ripe fruit. Blood glucose levels were measured using a calibrated glucometer (On Call Plus). The glycemic index (GI) and glycemic load (GL) were determined using standard methods. The results showed that mango juice had a moderate GI (56.41 ± 3.52) and a high GL (7.46 ± 0.47). Papaya, orange, and apple juices all had low GI (49.67 ± 5.05, 42.97 ± 2.93, and 31.50 ± 3.32, respectively) and low GL (4.23 ± 0.43, 3.91 ± 0.27, and 2.56 ± 0.38, respectively). This study indicates that although the GL of the fruit juices studied was low, particularly mango juice, should be consumed in moderation by diabetic subjects.